Pengaruh Marinasi Kulit Pisang Pada Olahan Daging Sapi Terhadap Kualitas Fisik dan Daya Terima Konsumen - Raihan Anugerah Pratama; Alsuhendra Alsuhendra; Ridawati Ridawati (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Abstract: This study aims to identify the effect of marination with Musa Paradisiaca L. (kepok) peel, Musa Acuminata Linn. (barangan), and Musa Paradisiaca L. Var Sapientum (raja bulu) on processed beef products on physical quality (tenderness) and consumer acceptability. The method used was experimental. The research was conducted at the State University of Jakarta with a sample of 30 Education of Culinary Arts students who were moderately trained panelists. Based on the statistical hypothesis test with the Friedman test, it can be seen that all aspects (color, taste, aroma and texture) are not affected by marination treatment in processed beef products on consumer acceptance. Based on the results of Anova calculation on physical quality test, there is a real difference in banana peel marination treatment on the level of meat tenderness.